Consensus of traditional knowledge on provisioning services of trees at farm in western Himalaya, India - Nagar, Bhuvnesh; Rawat, Sushma; Uthappa, A.R. (Indian Journal of Agroforestry, 2020)
A perception based study was conducted in Western Himalaya with the aim to document the indigenous knowledge of people on utilization and maintenance of cultural significance of useful agroforestry tree species by smallholders on their farmlands. Trees on farm are a promising alternative, and considered as one of the option to improve livelihood security of smallholders. This paper examines the potential role of trees at farm level in securing subsistence well-being of small holders, using semi-structured questionnaire in Alaknanda valley. The study compares two indices namely informant consensus and fidelity level of agroforestry tree species aiming to assess their cultural significance in livelihood security. Maximum informant consensus factor was recorded for fibre extraction (1.00) followed by ritual (0.982), food (0.981), fuelwood (0.977) and fodder (0.976) as well as fidelity level of species for assessing the importance of individual species in a particular use category. Thus the results of the study facilitates in increasing awareness of provisioning services of agroforestry tree species in supporting livelihood of mountainous smallholders.